2017
DOI: 10.1002/2016jd026333
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative precipitation estimates for the northeastern Qinghai‐Tibetan Plateau over the last 18,000 years

Abstract: Quantitative information regarding the long‐term variability of precipitation and vegetation during the period covering both the Late Glacial and the Holocene on the Qinghai‐Tibetan Plateau (QTP) is scarce. Herein, we provide new and numerical reconstructions for annual mean precipitation (PANN) and vegetation history over the last 18,000 years using high‐resolution pollen data from Lakes Dalianhai and Qinghai on the northeastern QTP. Hitherto, five calibration techniques including weighted averaging, weighted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 121 publications
1
37
0
Order By: Relevance
“…However, because the accumulation of sediments continued for ~5 ka, further mechanisms must be taken into account. First, the increase in moisture was a gradual process as indicated by various proxy records (Shen et al, 2005; Herzschuh, 2006; Li and Liu, 2017; Li et al, 2017). This resulted in a gradual reduction in sediment availability.…”
Section: Discussionmentioning
confidence: 99%
“…However, because the accumulation of sediments continued for ~5 ka, further mechanisms must be taken into account. First, the increase in moisture was a gradual process as indicated by various proxy records (Shen et al, 2005; Herzschuh, 2006; Li and Liu, 2017; Li et al, 2017). This resulted in a gradual reduction in sediment availability.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the range of NMRs in China is mainly based on the summer monsoon boundary proposed in 1962 by Gao et al (1962), which has been accepted by many researchers and is widely used in the climate research field (Chen et al 2016, Gao et al 2017, Li et al 2017 (figure 1). The NMR in China is mainly located in the western and northern parts of the country, with a range of 73°-121°E, 35°-53°N and an area of approximately 3.9×10 6 km 2 .…”
Section: Overview Of Study Areamentioning
confidence: 99%
“…Due to the applicability of microlithic technology in the harsh environment, a large number of microlithic sites were found in the QTP during the middle Holocene, such as Jiangxigou 2 34 and Yeniugou 35 . Additionally, quantitatively reconstructed precipitation based on pollen data from Lake Luanhaizi 36 , Lake Yidun 37 and Lake Qinghai 38 on the eastern QTP indicated that there was more precipitation in the early and middle Holocene 39 , less aeolian deposits weakly 40 , paleosols were formed mainly during 9.5–4.0 ka BP 41 . With the above background, QTP is likely to have seen the emergence of hunter-gatherers all year-round in the early and middle Holocene.…”
Section: Resultsmentioning
confidence: 99%